Sistem Pengontrolan Kendaraan Bermotor Jarak Jauh Berbasis GPS Tracker dan Mikrokontroller Pada Platform Android - Wahyudi Sofyan; Handy Ferdiansyah; Zulkifli N; Yulia Ekawaty; Hariani (INSOLOGI: Jurnal Sains dan Teknologi, 2022)
In every region, of course, it cannot be separated from the so-called motor vehicle theft that often occurs, of course, this causes anxiety for the majority of people who have motorized vehicles. This study aims to create a Remote Control Vehicle Application Based on GPS Tracker and Microcontroller on the Android Platform to be able to find out the location of the lost vehicle and to be able to control and monitor the vehicle through an android device. The system design starts from the design of the Ublox Neo-6m GPS module, SIM900A GSM / GPRS Mini, Relay, Stepdown, Arduino Uno R3 and Android applications that are used to control, track and monitor the vehicle. The results showed that the Remote Control Vehicle Application Based on GPS Tracker and Microcontroller on the Android Platform can track and monitor motorized vehicles in case of loss through the GPS module. The results of this study are to minimize the theft of motor vehicles in an effort to prevent theft and loss of vehicles for vehicle owners.